2021
DOI: 10.1007/s13178-021-00589-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Adolescents and Young Adults Learn About Condoms from Healthcare Providers? Findings from a US Probability Sample

Abstract: Introduction: Using data from the 2018 National Survey of Sexual Health and Behavior, we determined the prevalence and content of adolescents' and young adults' communication with healthcare providers about condom use.Methods: Adolescents (14-17 years-old; n = 283) and young adults (18-24 years-old, n = 225), who discussed sexual health with a healthcare provider in the past-year, reported if they had discussed condom use with a healthcare provider and among those who did, they also reported why healthcare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, this study's findings showed that neither girls nor boys consulted teachers or doctors/ nurses for sexual information. Adolescents clearly are not using healthcare professionals as resources for sexual information (Beckmeyer et al, 2021). Perhaps, if healthcare professionals were used as resources, the level of sexual knowledge among high school students would be better.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study's findings showed that neither girls nor boys consulted teachers or doctors/ nurses for sexual information. Adolescents clearly are not using healthcare professionals as resources for sexual information (Beckmeyer et al, 2021). Perhaps, if healthcare professionals were used as resources, the level of sexual knowledge among high school students would be better.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies comparing the sexual risk counseling practices of rural and urban PCPs do not exist, so there are difficulties comparing study findings to the literature. However, prior research has noted that many PCPs do not provide sexual risk reduction counseling, 23,24 are unknowledgeable and uncomfortable discussing sexual health, 25 do not talk to adolescents about condom use, 26 and do not provide rural sexual minority male (SMM) patients individual HIV prevention counseling 27 and PrEP discussions 28 . Medical students in Oklahoma, an EHE rural‐burden state, noted they do not receive education about HIV prevention/PrEP and are uncomfortable discussing sexual health with patients 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is important to ensure youth have time alone with providers to discuss their health and well-being (Coker et al, 2010). Private face-to-face discussions with providers can help youth feel comfortable and reassured about the confidentiality of their disclosures regarding pertinent information (including sexual health, mental health challenges, drug [mis]use, or engagement in risky behaviors; Beckmeyer, Patterson, et al, 2022; Coker et al, 2010; Liddon et al, 2021).…”
mentioning
confidence: 99%